2016
DOI: 10.1038/srep22876
|View full text |Cite
|
Sign up to set email alerts
|

Metal-Diazo Radicals of α-Carbonyl Diazomethanes

Abstract: Metal-diazo radicals of α-carbonyl diazomethanes are new members of the radical family and are precursors to metal-carbene radicals. Herein, using electron paramagnetic resonance spectroscopy with spin-trapping, we detect diazo radicals of α-carbonyl diazomethanes, induced by [Rh Radicals are highly reactive intermediates, long sought because of their importance in understanding reaction mechanisms and finding new reactions 1 . However, their extremely short lifetimes make their direct detection difficult and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…The SNOs of 1OS RC-EDA close reveal that iron donates electron density to EDA (Figure a). Recent reports similarly found spin density on the N 2 moiety of rhodium and copper alkyl diazoacetate systems. , This interaction leads to a significant Fe–C bond, of 2.23 Å. This electron donated from iron to EDA enters a C–N antibonding orbital, resulting in a significantly longer C–N distance in 1OS RC-EDA close than in 1CS RC-EDA far (Table S11).…”
Section: Resultsmentioning
confidence: 69%
“…The SNOs of 1OS RC-EDA close reveal that iron donates electron density to EDA (Figure a). Recent reports similarly found spin density on the N 2 moiety of rhodium and copper alkyl diazoacetate systems. , This interaction leads to a significant Fe–C bond, of 2.23 Å. This electron donated from iron to EDA enters a C–N antibonding orbital, resulting in a significantly longer C–N distance in 1OS RC-EDA close than in 1CS RC-EDA far (Table S11).…”
Section: Resultsmentioning
confidence: 69%
“…13 Analysis of the reaction mixture in both Fe-catalyzed systems by time-and temperature-dependent electron paramagnetic resonance (EPR) studies showed no signals that would be expected to arise from radical species generated in a MHAT process (see the Supporting Information for details). Control experiments with (2,2,6,6-tetramethylpiperidin-1-yl)oxyl (TEMPO) or 5,5-dimethyl-1-pyrroline N-oxide (DMPO) 14 also did not support the possibility of related radical intermediates (see the Supporting Information for details).…”
Section: ■ Results and Disussionmentioning
confidence: 99%
“…The DMPO-X 1 (♥) signal with a single nitrogen (a N = 16.50 G (16.30–16.60), a triplet 1:1:1) [44] may contribute from the oxidation of DMPO itself, but according to study of Kondo et al [45] , peaks labeled “♥” may be due to DMPO•-H adducts showing a primary triplet (a N = 16.50 G) further split by two secondary hydrogens (⋄, a H β = 22.40 G). From Fig.…”
Section: Resultsmentioning
confidence: 99%